Hubungan Dukungan Sosial Dengan Self-EfficacyIbu Postpartum - Desiana Rachmawati; Lina Ayu Marcelina; Indah Permatasari (Poltekkes Kemenkes Jakarta III, 2021)
Maternal self-efficacy is part of the concept of self-efficacy which is the mother's belief in her Maternal self-efficacy is part of the concept of self-efficacy which is the mother's belief in her ability to carry out her role as a parent, one of which can be influenced by social support. Social support arises because of interactions with other people who make a person feel cared for and appreciated, if social support is not obtained by postpartum mothers, the possibility of mothers experiencing postpartum depression will increase. The crisis period in the midst of the COVID-19 pandemic raises concerns, especially for postpartum mothers because of limited access to formal and informal support which will increase maternal mental health problems. The research design used was cross sectional. The population of this study, namely all postpartum mothers in the Pejuang Health Center Work Area, Bekasi City, amounted to 132 people and obtained a total sample of 116 respondents through a sampling technique, namely accidental sampling. Data analysis used chi-square at 95% confidence level. The results of this study showed a significant relationship between social support and MSE (p = 0.038). It is hoped that health services can increase their participation in providing counseling based on family support for postpartum mothers by including the family to have a positive effect on the bond between mother and baby.